2018
DOI: 10.1039/c7nr09081a
|View full text |Cite
|
Sign up to set email alerts
|

Metal organic frameworks as a catalyst for oxygen reduction: an unexpected outcome of a highly active Mn-MOF-based catalyst incorporated in activated carbon

Abstract: Owing to their unique chemistry and physical properties, metal-organic frameworks (MOFs) are an interesting class of materials which can be utilized for a wide array of applications. MOFs have been proposed to be used as catalysts for fuel cells, but their low intrinsic electronic conductivity hampered their utilization as is. In this work, we present the synthesis and application of MOF-based precious-metal-group-free (PGM-free) catalysts for oxygen reduction based on a unique metal-organic framework-carbon c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
41
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 50 publications
4
41
0
Order By: Relevance
“…Ag‐BTC and Ag‐BTC@AC were synthesized according to the procedure described in the experimental section. Two‐probes bulk conductivity measurements showed that the AgBTC is practically an insulator, as many other metal‐BTC, unlike the high electronic conductivity of metallic silver. Therefore, AgBTC cannot be utilized as a stand‐alone electrocatalyst/electrode in its pristine form.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Ag‐BTC and Ag‐BTC@AC were synthesized according to the procedure described in the experimental section. Two‐probes bulk conductivity measurements showed that the AgBTC is practically an insulator, as many other metal‐BTC, unlike the high electronic conductivity of metallic silver. Therefore, AgBTC cannot be utilized as a stand‐alone electrocatalyst/electrode in its pristine form.…”
Section: Resultsmentioning
confidence: 99%
“…), metal organic frameworks (MOFs) of metal ions coordinated by polydentate ligands, or heat‐treated materials (M−N−C) . In many cases, macrocyclic compounds and MOFs have been used as the precursor to the M−N−C catalysts rather than being the catalyst itself, since the heat‐treatment raises their overall performance, and due to the lack of conductivity and stability in many cases . The most common metals used in PGM‐free catalysts are first‐row transition metals, usually iron or cobalt …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has also been confirmed in Mn−Co spinel oxide compounds that those having largest ratio of Mn 4+ /Mn 3+ has the highest ORR activity . Also, manganese‐based bifunctional ORR and OER catalytic activity have been reported for α‐MnO 2 , layered manganese oxides, cobalt manganese oxides, CoMn 2 O 4 embedded MnOOH nanorods and even in multiple transition metal‐based composites like FeCoNiMn‐nanocarbon, manganese doped multi‐metallic oxysulfide nanoparticles, Mn plays the most important role in bifunctional activity and stability . Additionally, the Jahn‐teller distortion and back bonding with a change in bond length have been observed both in manganese and phosphate‐based materials and hence might boost the kinetics of ORR activity .…”
Section: Introductionmentioning
confidence: 99%